Marines at War Stories from Afghanistan and Iraq - Tripodi, Paolo G.; Frushour, Kelly (Marine Corps University Press (MCUP), 2016)
This book brings together the short stories of 10 Marines and a sailor who served in either Afghanistan or Iraq, some in both. The authors reflect on their time in combat, focusing on preparation, particular moments, and the lessons or conclusions drawn from their experiences. While every servicemember has a different story, and despite these remembrances being very personal, this collection represents and provides insight into the ordinary experiences of fellow Americans serving during an extraordinary set of circumstances. That set of circumstances is obviously war. War, for the modern American, is the monotony of everyday life lived far away from home, broken up by intense moments of fear, conflict, and violence. This collection examines both the monotony and the intense moments that these men and women experienced from a diverse set of perspectives.